Recent Advances in Strain-Induced Piezoelectric and Piezoresistive Effect-Engineered 2D Semiconductors for Adaptive Electronics and Optoelectronics - Li, Feng; Shen, Tao; Wang, Cong; Zhang, Yupeng; Qi, Junjie; Zhang, Han (Nano-Micro Letters, 2020)
The development of two-dimensional (2D) semiconductors has attracted widespread attentions in the scientific community and industry due to their ultra-thin thickness, unique structure, excellent optoelectronic properties and novel physics. The excellent flexibility and outstanding mechanical strength of 2D semiconductors provide opportunities for fabricated strain-sensitive devices and utilized strain tuning their electronic and optic–electric performance. The strain-engineered one-dimensional materials have been well investigated, while there is a long way to go for 2D semiconductors. In this review, starting with the fundamental theories of piezoelectric and piezoresistive effect resulted by strain, following we reviewed the recent simulation works of strain engineering in novel 2D semiconductors, such as Janus 2D and 2D-Xene structures. Moreover, recent advances in experimental observation of strain tuning PL spectra and transport behavior of 2D semiconductors are summarized. Furthermore, the applications of strain-engineered 2D semiconductors in sensors, photodetectors and nanogenerators are also highlighted. At last, we in-depth discussed future research directions of strain-engineered 2D semiconductor and related electronics and optoelectronics device applications. Highlights: 1 A comprehensive review of strain-engineered 2D semiconductors in electronics and optoelectronics. The basic theories and simulation studies of strain introduced piezoelectric effect and piezoresistive effect have been summarized. 2 The various experimental methods for study strain-engineered 2D semiconductors have been highlighted. 3 The applications of strain sensor, strain tuning the performance of photodetector and piezoelectric nanogenerator have been reviewed.